Patient navigation services for cancer care in low-and middle-income countries: A scoping review. - Milena Dalton; Emily Holzman; Erica Erwin; Sophia Michelen; Anne F Rositch; Somesh Kumar; Verna Vanderpuye; Karen Yeates; Erica J Liebermann; Ophira Ginsburg (PLoS ONE)
Background Nearly 70% of all cancer deaths occur in low- and middle-income countries (LMICs) and many of these cancer deaths are preventable. In high-income countries (HICs), patient navigation strategies have been successfully implemented to facilitate the patient's journey at multiple points along the cancer care continuum. The purpose of this scoping review is to understand and describe the scope of patient navigation interventions and services employed in LMICs. Methods A systematic search of published articles was conducted including Medline, Biosis, Embase, Global Health, and Web of Science. Articles were examined for evidence of patient navigation interventions used in cancer care in LMICs. Evidence was synthesized by navigation service provided and by type of outcome. Results Fourteen studies reported on patient navigation interventions in cancer care in low-income and middle-income countries in Asia, South America, and Africa. Most studies reported on women's cancers and included navigation interventions at most points along the cancer care continuum i.e. awareness, education, screening participation, adherence to treatment and surveillance protocols. Conclusion Few studies report on cancer patient navigation in LMICs. With the use of an implementation science framework, patient navigation research can explore a broader range of outcomes to better evaluate its potential role in improving cancer control in LMICs.